(untitled) (Saúde Ética & Justiça, 2003)
The interdiction to the incest is fundamental in the human being development, at the individual and family levels, as well as in regard to the social aspect. It postulates limits, defines the generations and introduces the possibility of social and mental organization. Parents have a special role in child development. They are the main figures in the child’s first sexual fantasies, which configure the Oedipus Complex. The incest action represents the factual realization of such prohibited impulses, which should be repressed. Such fact increases the violence of this kind of sexual abuse. In the incest between father and daughter the emotional consequences depend on several factors and can vary a lot. In spite of such variety of consequences it’s possible to associate the occurrence of the incest to a higher difficulty in integrating mental contents by the child. The care in the incest situation must include the intervention of mental health professionals as well as the intervention of the Law.